EVALUATING THE RISK OF HYPERTENSION DEVELOPMENT IN THE CONTEXT OF PERIODONTITIS - Oana-Maria Butnaru; Diana Tatarciuc; Mihai Ştefan Cristian Haba; Dana Budală; Ana Sîrghe; Liliana Păsărin; Ionuț Luchian; Danisia Haba (Romanian Society of Oral Rehabilitation, 2024)
This study investigates the potential link between periodontitis and the development of hypertension, aiming to assess the risk of hypertension in individuals with periodontal disease. Periodontitis, a chronic inflammatory condition affecting the supporting structures of teeth, has been increasingly associated with systemic health issues, including cardiovascular diseases. We conducted a comprehensive review of existing literature and analyzed data from clinical studies to evaluate the prevalence and severity of hypertension in patients with periodontitis. Our findings suggest a significant correlation between periodontal inflammation and elevated blood pressure, highlighting the role of systemic inflammation as a contributing factor. The study emphasizes the importance of early diagnosis and management of periodontitis as a potential strategy to mitigate the risk of hypertension. Further research is recommended to explore the underlying mechanisms and to develop integrated approaches for the prevention and treatment of both conditions. This investigation underscores the need for interdisciplinary collaboration between dental and medical professionals to enhance patient care and outcomes.